Profiling for primary-care presentation, investigation and referral for liver cancers: evidence from a national audit. Issue 4 (April 2016) - Hughes, Daniel L.; Neal, Richard D.; Lyratzopoulos, Georgios; Rubin, Greg
Abstract : Background and aim: The incidence of liver cancer across Europe is increasing. There is a lack of evidence within the current literature on the identification and investigation of liver cancer within primary care. We aimed to profile liver cancer recognition and assessment as well as the timeliness of liver cancer diagnosis from within the primary-care setting in the UK. Methods: Data were obtained from the National Audit of Cancer Diagnosis in Primary Care 2009–2010 and analysed. We calculated the patient interval, the primary-care interval and the number of prereferral consultations for liver cancer. We then compared these data with prior data on the respective indicators for other common cancers. Results: The median patient interval was 9 days (interquartile range 0–31 days), and the median primary-care interval for liver cancer was 11 days (interquartile range 0–40 days). Of the 90 patients, 21 (23.3%) had three or more consultations with their general practitioner before specialist referral. For the three metrics (patient interval, primary-care interval and number of prereferral consultations), liver cancer has average or longer intervals when compared with other cancers. The most common symptomatic presentation of liver cancer within the primary-care setting was right upper quadrant pain (11%), followed by decompensated liver failure (9%). Of the patients, 12% were diagnosed with liver cancer on the basis of an incidental finding of an abnormal liver function test. Conclusion: This study provides a detailed and thorough overview of the recognition of liver cancer and the promptness of liver cancer identification in an English context, and should inform strategies for improving the timeliness of diagnosis.